2014
DOI: 10.1016/j.rbmo.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

WNT9B in 542 Chinese women with Müllerian duct abnormalities: mutation analysis

Abstract: The WNT9B gene is a common organizing signal regulating different segments of the mammalian urogenital system and plays a primary role in the development of the female reproductive tract. The aim of the present work was to examine the presence of WNT mutations in a population of women with Müllerian duct abnormalities (MDA) in order to elucidate whether mutations in WNT9B are causative for MDA in Chinese women. Initially, 191 Chinese MDA patients and 192 healthy individuals (controls) were recruited. All codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…However, it is unclear whether the mutations were found in trans or in cis. Tang et al (2014) found the two novel WNT9B variants c.566G>A (p.Arg189Gln) and This patient additionally has a likely pathogenic missense mutation in TBX6.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, it is unclear whether the mutations were found in trans or in cis. Tang et al (2014) found the two novel WNT9B variants c.566G>A (p.Arg189Gln) and This patient additionally has a likely pathogenic missense mutation in TBX6.…”
Section: Discussionmentioning
confidence: 84%
“…However, it is unclear whether the mutations were found in trans or in cis . Tang et al (2014) found the two novel WNT9B variants c.566G>A (p.Arg189Gln) and c.773G>A (p.Arg258His) in a first stage analysis of 191 Chinese women with MD anomalies . In a second stage analysis, 351 additional cases and 563 controls were screened for the presence of these two WNT9B variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the known reasons such as environmental factors, harmful hormones, ionizing radiation, and drug effects, genetic factors may act as the major cause of MDA [4][5][6]. In the recent two decades, a lot of essential candidate genes related to the development of the mullerian duct have been studied, such as the WNT and HOX families, LHX1, and TBX6 [7][8][9][10][11][12][13][14]. However, most of the researches failed to explain the relationship between the genes and MDA.…”
Section: Introductionmentioning
confidence: 99%